2016
DOI: 10.1002/stem.2447
|View full text |Cite
|
Sign up to set email alerts
|

Positive Feedback Loop of OCT4 and c-JUN Expedites Cancer Stemness in Liver Cancer

Abstract: The network of stemness genes and oncogenes in human patient-specific reprogrammed cancer stem cells (CSCs) remains elusive, especially in liver cancer. HepG2-derived induced pluripotent stem cell-like cells (HepG2-iPS-like cells) were generated by introducing Yamanaka factors and the knockdown vector shTP53. They exhibited features of stemness and a higher tumorigenesis after xenograft transplantation compared with HepG2 cells. The cancerous mass of severe combined immunodeficiency (SCID) mice derived from on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 45 publications
(61 reference statements)
1
56
0
Order By: Relevance
“…41 Elevated expression of KLF-4 in HCC is significantly correlated with poor tumor differentiation, vascular invasion, overall survival, and recurrence-free survival. 22 As a major pluripotent factor, Oct-4 is highly expressed in liver CSCs [42][43][44] and may contribute to the reprogramming of CSCs. Gli-1 is the main transcription factor in hedgehog signaling pathway, which is activated in various chronic liver diseases.…”
Section: Discussionmentioning
confidence: 99%
“…41 Elevated expression of KLF-4 in HCC is significantly correlated with poor tumor differentiation, vascular invasion, overall survival, and recurrence-free survival. 22 As a major pluripotent factor, Oct-4 is highly expressed in liver CSCs [42][43][44] and may contribute to the reprogramming of CSCs. Gli-1 is the main transcription factor in hedgehog signaling pathway, which is activated in various chronic liver diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Heterogeneity of cancer cells in the same patient can arise for multiple reasons [5860]. First, heterogeneity can be generated by stochastic genetic [61] or epigenetic changes [62].…”
Section: Advantages Provided For Cancer Research By Cancer Cell Repromentioning
confidence: 99%
“…These iPSC-like cells were more sensitive to 5-fluorouracil and drugs of differentiation–induction and exhibited reduced tumorigenicity in nonobese diabetic/severe combined immunodeficient mice. Kuo et al [58] found that the positive feedback between OCT4 and c - JUN increased with the onset of cancers. We hypothesized that the positive feedback regulation of OCT4 and c-JUN might promote the generation of liver CSCs.…”
Section: Advantages Provided For Cancer Research By Cancer Cell Repromentioning
confidence: 99%
See 1 more Smart Citation
“…These result further indicate the importance of OCT4 contributing to the development of cancers in a number of ways (18,19). The aim of the present study was to investigate the role of miR-145 in the modulation of cervical cancer cell radiosensitivity, using transfection with miR-145 mimics to upregulate miR-145 in cervical cancer tera cells.…”
Section: Microrna-145 Sensitizes Cervical Cancer Cells To Low-dose Irmentioning
confidence: 91%